Tailoring potential antigenic regions on pandemic SARS spike protein - Hoa, Le Thanh; Thong, Le Nhat; Thong, Le Minh (Vietnam Journal of Biotechnology, 2024)
Coronavirus-associated severe acute respiratory syndrome (SARS) pandemics have devastated lives, economies, and societies worldwide. Given the higher severity of the latter pandemic, the constant mutation, and vaccine escape, new and more dangerous pandemics could emerge. Therefore, it is imperative to identify conserved vaccine candidates for stable effectiveness in future pandemics. This study aimed to tailor potential, conserved peptide-based vaccine candidates for the upcoming Coronavirus pandemic based on the sequences of the spike protein of SARS-CoV-1 and SARS-CoV-2 viruses, using bioinformatic approaches. Peptide-based CD4+ T-cell epitopes derived from SARS proteomes were identified based on their predicted binding affinity to HLA-DRB1, one of the central molecules for the adaptive immune system. These epitopes were then assessed for conservation by sequence analysis of all pandemic-involved strains and variants. The epitopes were then evaluated and cross-checked for possible protection against the causative pathogens via potential uptake by B-cell receptors, the sustenance of sequence conservation for the future pandemic strain using data from population HLA-allele-typing studies, structural analysis of the spike-antibody complex and their contribution to the function of spike protein, respectively. As a result, selected vaccine candidates were projected to cover nearly 90% of the world’s population with the combination of just four epitopes. The epitopes could be modified to adapt to future pandemic strains, improve antigenicity, or be used as booster immunization against the currently circulating SARS-CoV-2 variant. This study demonstrates that there is still room for improvement and promising discoveries in vaccine design to deter upcoming SARS pandemics.